التزامات نادي كرة القدم في مواجهة اللاعبين المحترفين - حامد صاروة, هيثم; سعيد الرفاعي, عمار (جامعة الوادي University of Eloued, 2017)
يترتب على نادي كرة القدم العديد من الالتزامات في مواجهة لاعبيه المحترفين؛ إذ يتوجب عليه بمجرد إبرام العقد بينهما الالتزام بأداء الأجر للاعب وتوفير تأمين صحي له، إضافة إلى تسجيله لدى الاتحاد العربي السعودي لكرة القدم وتمكينه من اللعب لحساب النادي والمنتخبات الوطنية، والنادي إذ يقوم بهذه الالتزامات في مواجهة لاعبيه المحترفين الذين يعدون قوام نشاطه الكروي، فإنما يقوم بها لمصلحة تعود عليه وتنفيذا للعقد المبرم بينه وبين اللاعب وبما لا يخرج أو يقل عما هو مقرر في لائحة الاحتراف وأوضاع اللاعبين وانتقالاتهم في المملكة العربية السعودية، فقد تولت هذه اللائحة بيان العديد من الجوانب المتعلقة بهذه الالتزامات، غير أن تعارض المصالح وتضاربها يبقى أمراً متاحا. وقد حاولت هذه الدراسة بيان ومناقشة التزامات النادي المستحقة للاعب المحترف وفقا للائحة الاحتراف، لا سيما بشأن بعض المسائل التي قد يشوبها النقص أو الغموض، حيث انتهت إلى جملة من النتائج والتوصيات. Abstract: Once a football club sign a professional contract with a professional player, the club is committed to a number of commitments in the face of this player, first of all, the club must performance the agreed wage to the player, secure health insurance for him, record him in the Saudi Arabian Football Federation, enable him to play for the benefit of the club and the national team, When the club carry out these commitments, It is do it for its interest, and application of the contract signed between him and the player, this agreement does not come out of “the regulation of professionalism and the conditions of the players and their move in Saudi Arabia”, this regulation has assumed clarify many aspects related to these obligations, but the conflict of interest and incongruent remain available. This study attempted to clarify and discuss the Obligations of club due to the professional player, according to the regulation of professionalism, especially about some of the issues, that may be marred by shortages or ambiguity, where over to a series of conclusions and recommendations.
دراسة تحليلية في لائحة الاحتراف وأوضاع اللاعبين وانتقالاتهم في السعودية
Keywords: عقد الاحتراف؛ اللاعب المحترف؛ حقوق اللاعب؛ التزامات النادي